2018
DOI: 10.1002/2017ja024938
|View full text |Cite
|
Sign up to set email alerts
|

A Sporadic Topside Layer in the Ionosphere of Mars From Analysis of MGS Radio Occultation Data

Abstract: The topside ionosphere of Mars is subject to dynamic interactions between the planet and the surrounding space environment. Significant variations in its structure have been observed that have not been consistently investigated or explained. All 5,600 ionospheric profiles obtained by the Mars Global Surveyor Radio Science experiment are analyzed here to systematically characterize a topside ionospheric layer that is visible in ~50% of the observations. For simplicity, we refer to this layer of plasma as the M3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 104 publications
(237 reference statements)
0
8
0
Order By: Relevance
“…Follow-up studies using multiparameter observations from MAVEN, plus 1-D modeling, indicated two types of N e enhancements at the height of the M3-layer: (1) photo-ionization of localized enhancements in the neutral atmosphere, and (2) enhancements due to other processes (e.g., field-aligned-currents, electron precipitation, solar wind interactions, and plasma instabilities). The first category identified by Mayyasi et al (2018) is classic PCE physics involving photo-ionization of the neutral atmosphere (more CO 2 →more N e )-referred to as the "coupled" case. The second category was called "uncoupled" because there is no CO 2 (h) signature simultaneously evident with the observed N e (h) feature.…”
Section: Structures In the Topside Ionosphere Of Marsmentioning
confidence: 99%
See 4 more Smart Citations
“…Follow-up studies using multiparameter observations from MAVEN, plus 1-D modeling, indicated two types of N e enhancements at the height of the M3-layer: (1) photo-ionization of localized enhancements in the neutral atmosphere, and (2) enhancements due to other processes (e.g., field-aligned-currents, electron precipitation, solar wind interactions, and plasma instabilities). The first category identified by Mayyasi et al (2018) is classic PCE physics involving photo-ionization of the neutral atmosphere (more CO 2 →more N e )-referred to as the "coupled" case. The second category was called "uncoupled" because there is no CO 2 (h) signature simultaneously evident with the observed N e (h) feature.…”
Section: Structures In the Topside Ionosphere Of Marsmentioning
confidence: 99%
“…The first category identified by Mayyasi et al. (2018) is classic PCE physics involving photo‐ionization of the neutral atmosphere (more CO 2 →more N e )—referred to as the “coupled” case. The second category was called “uncoupled” because there is no CO 2 (h) signature simultaneously evident with the observed N e (h) feature.…”
Section: Additional Analysismentioning
confidence: 99%
See 3 more Smart Citations